PEMBUATAN WEBSITE AKADEMIK PADA SMA YADIKA 2 - Yunika, emmi (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Academic information system at High School Yadika 2 still done manually. In the data processing is still in the conventional academic with the current data collection system is felt still many shortcomings that happened, because the existing systems still use paper and archival sheet so as to cause the existing data is easily lost or damaged. Development of systems in the form of making a web-based information systems academic at Public High Schools 1 Ngadirojo an information system that provides reports online activity of students in the form of reports student grades and attendance report is concerned with web-based, so it helps the speed and quality in the delivery of information. In addition to the web-based data information can be accessed at a time and place not specified. In this system, the menu can only be accessed by certain users, namely students, teachers and administrators. Information system academic was built using the PHP programming language with database MySql. Expected this System can assist to facilitate the performance of all officer in High School Yadika 2.